Monitoring of Pathogen-Specific T-Cell Immune Reconstitution after Allogeneic Hematopoietic Stem Cell Transplantation - Fuji, Shigeo; Kapp, Markus; Einsele, Hermann (Frontiers in Immunology, 2013)
The clinical outcome after allogeneic hematopoietic stem cell transplantation (HSCT) has been significantly improved during the last decades with regard to the reduction in organ failure, infection, and severe acute graft-versus-host disease (GVHD). However, severe complications due to infectious diseases are still one of the major causes of morbidity and mortality after allogeneic HSCT, in particular in patients receiving haploidentical HSCT or cord blood transplant due to a slow and often incomplete immune reconstitution. In order to improve the immune control of pathogens without an increased risk of alloreactivity, adoptive immunotherapy using highly enriched pathogen-specific T cells offers a promising approach. In order to identify patients who are at high risk for infectious diseases, several monitoring assays have been developed with potential for the guidance of immunosuppressive drugs and adoptive immunotherapy in clinical practice. In this article, we aim to give a comprehensive overview regarding current developments of T-cell monitoring techniques focusing on T cells against viruses and fungi. In particular, we will focus on rather simple, fast, non-labor-intensive, cellular assays which could be integrated in routine clinical screening approaches.